Identification of quorum signal antagonists in dietary plants in Sabah, Malaysia - Senty Vun Sang (2014)
Recent discovery has demonstrated that many pathogenic bacteria employ quorum sensing (QS) to modulate their morbific agents and virulence production. This finding has evoked ideas that the interruption of QS in a pathogen may result in decreased virulence production and is a potential strategy in attenuating bacterial infections. This study involved the investigation of 50 Malaysian dietary plants via aqueous and ethanolic extraction for potential QS inhibition activity particularly against QS regulated swarming motility and biofilm formation against two bacterial pathogens Escherichia coli O157:H7 and Pseudomonas aeruginosa PAO1. At sublethal concentrations, out of the 50 plants screened, aqueous extracts of Kaempferia galangal and Sygzium aromaticum and ethanolic extracts of Camellia sinensis, and Polygonum minus were found to exhibit QS inhibition activity via the Chromobacterium violaceum assay. All plants extracts tested in this study show varying degree of inhibition and enhancement in QS regulated swarming motility and biofilm formation. P. aeruginosa PAO1 consist of two QS system which is las (lasI-lasR) and rhl (rhlI-rhlR) system, which is consist of autoinducer synthase and transcriptional activator respectively. These QS system control in the regulation and expression of numerous virulence genes. The up-regulation and down-regulation of these genes will activate or repress a series of downstream genes hence influence in the expression and virulence production of the bacteria. Genetic expression studies via quantitative real-time PCR on Pseudomonas aeruginosa PAO1 QS gene showed that selected plants extracts of Camellia sinensis, Kaempferia galangal, Polygonum minus and Syzygium aromaticum up-regulated lasR, rhlI and rhlR gene expression from 0.5 to 7.9 fold and down-regulated lasI, lasR and rhlR gene from - 0.2 to -2.6 fold. The findings of these studies justify further investigation to explore the potential of Malaysian dietary plants with GRAS (Generally Regarded as Safe) properties as potential QS inhibitors and as an alternative strategy in further antibacterial management therapy.